Heterogeneity of tumour response to hypoxia: carbonic anhydrase IX induction defines a subpopulation of hypoxic cells with stem cell properties and drug resistance - Ledaki, I (2013)
Carbonic anhydrase IX (CA9) is strongly induced by hypoxia and its overexpression is associated with poor therapeutic outcome in cancer. The function of CAIX is to catalyze the reversible hydration of CO2 to bicarbonate and a proton. This helps hypoxic tumours to maintain a more neutral intracellular pH (pHi) promoting survival, but produces a more acidic extracellular (pHe) which promotes invasion and metastasis. Recent evidence has expanded on the role of hypoxia and CAIX by relating them to stem cell niches. In this study, taking advantage of the transmembrane location of CAIX, we show for the first time, a direct marked heterogeneity in response to hypoxia within each tumour cell population studied, associated with major biological differences. Based on CAIX expression pattern under hypoxic conditions, we identify, isolate and characterize two distinct populations of tumour cells, one that express CAIX and the other that does not. Interestingly, we discover that the CAIX positive population is enriched with cells expressing cancer stem cell markers. These include ALDHA1, IGF1, LIN28 and genes involved in epithelial-mesenchymal transition (EMT) and multi-drug resistance (i.e. WNT2, TWIST1, and ABCC2). Accordingly, CAIX+ve cells show higher self-renewal capacity and form tumours significantly faster compared to the CAIX-ve population. Importantly, functional suppression of CAIX in vitro and in vivo, in two breast cancer cell lines resulted in the downregulation of breast cancer stem cell signatures, suggesting that CAIX is not just a marker of stemness but also a regulator of stemness. The molecular mechanism underlying the differential expression of CAIX in the two populations is not HIF-1α-dependent, but instead driven by hypoxia-induced reorganization of chromatin structure. In line with this, we provide experimental evidence showing that the genomic locus encoding CA9 has a more “open” and transcriptionally active chromatin structure in CAIX+ve cells, and a condense and transcriptionally silent chromatin structure in the CAIX-ve cells. Given that HIF induces the transcription of CA9 by binding to hypoxia response elements (HREs) in its promoter we show a significant reduction in binding of HIF to the CA9 promoter of the negative population. We suggest that the reduce HIF binding is a result of the compact chromatin structure of CA9 promoter of the negative cells. Analysis of the transcriptome of the positive and negative populations suggests a symbiotic relationship between these two subpopulations and their environment, likely required to promote tumour growth. This is based on the following observations: Firstly, we identified that CAIX-ve cells express high levels of cytokines and based on this, we suggest that the cytokines secreted by CAIX-ve cells may transmit paracrine signals that regulate the CAIX+ve cells, thus providing a wider hypoxia tolerant microenvironment to protect the stem cell population. Secondly, we identified a metabolic heterogeneity between the CAIX+ve and CAIX-ve cells. The CAIX+ve cells show an upregulation of genes implicated in oxidative phosphorylation, TCA cycle and fatty acid synthesis. Whereas in CAIX-ve cells there is an upregulation of genes implicated in autophagy and mitophagy. Given the above together with the upregulation of oxidative phosphorylation and TCA cycle in the CAIX+ve cells, we proposed the existence of a metabolic symbiosis between the CAIX+ve and CAIX-ve cells. We postulate that the catabolic process such as autophagy and mitophagy in the CAIX-ve cells may results in the overproduction of high-energy metabolites such as lactate, glutamine and ketone bodies which in turns they are been utilized by CAIX+ve cells to fuel mitochondria respiration. Finally, we also demonstrated that in the CAIX+ve cells mTORC1 signaling is upregulated, and contributes to the regulation of CAIX expression. Given the role of mTORC1 in stem cell maintenance and EMT as well as the interdependence of mTORC1 and CAIX expression in the CAIX+ve cells we suggest that mTORC1 signaling may be the critical factor by which CAIX regulates stemness. Interestingly, the subpopulations show a differential sensitivity to HDAC inhibitors, NaBu and SAHA as treatment of MCF7 breast cancer cell line and HCT116 colon cancer cell line leads to elimination of the CAIX+ve population. This is not driven by the downregulation of HIF-1α, the major transcriptional regulator of CAIX. In contrast, we demonstrate that SAHA causes downregulation mTORC1. This suggests that SAHA-induced downregulation of CAIX expression could be due to its effect on mTORC1 pathway. Of wider significance, our findings show that tumours are not homogenous in their response to hypoxia, and distinct signal transduction networks regulate different populations of cells within the tumour. This highlights the need for the utilization of biomarkers, which reveal distinct functional hypoxia profiles of human cancers, and permit the stratification of tumours. Furthermore, the identification of epigenetic regulation of the histones in response to hypoxia for highly selective gene regulation, provides a connection between the epigenetic mechanisms under environmental stress and cancer progression, and is model for development of novel epigenetic cancer therapeutic drugs.